ANALYSIS OF LIQUIDITY RATIO TO MEASURE FINANCIAL PERFORMANCE - Isna Ardila; Siti Aisyah Siregar (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the financial performance of PT. Garuda Indonesia Tbk with using liquidity ratio analysis for the period 2017 to 2020. Ratio The liquidity used to measure financial performance is the Current Ratio and Cash Ratio. The data used in this study are in the form of financial statement data taken from the annual report of PT Garuda Indonesia, Tbk for 4 years. The data analysis method used is the analytical method horizontally, which compares financial statements for certain time periods. From the data analysis, it can be seen that the liquidity ratio of PT. Garuda Indonesia Tbk in the last 4 (four) years seen from the current ratio in 2017-2018 was 51.35%, 55.36%, 33.39%, and 12.49%. The results of the calculation of the cash ratio in 2017-2020 are 7.35%, 5.76%, 8.98%, and 4.69%. This indicates that the current ratio and cash ratio PT. Garuda Indonesia Tbk in unfavorable circumstancesKeywords: Liquidity Ratio, Current Ratio, Cash Ratio